2020
DOI: 10.1186/s13037-020-00233-x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of pre-hospital pelvic circumferential compression devices for pelvic fractures: survey of U.S. level I trauma centers

Abstract: Introduction: There is a lack of data on the use and effectiveness of pre-hospital pelvic circumferential compression devices (PCCD) as a temporary intervention for pelvic fracture management; they are thought to decrease pelvic volume and hemorrhage but are not without risks. The purpose of this study is to examine prehospital PCCD practices at US Level I trauma centers. Methods: This was a prospective cross-sectional survey of trauma medical directors at US Level I trauma centers. The aim of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The use of pelvic compression devices such as binders is recommended as an early strategy to stabilize the pelvic ring and decrease the amount of pelvic hemorrhage in managing pelvic fractures (Coccolini et al, 2017; Jarvis et al, 2020; Pap et al, 2020). A study of inhospital and prehospital pelvic compression device use at U.S. Level I trauma centers found that prehospital pelvic compression devices were not applied to all suspected pelvic fractures (Jarvis et al, 2020). Similarly, Kuner found that only one-third of patients with pelvic fractures assigned to the resuscitation room of a Level I trauma center had a pelvic compression device applied (Kuner et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The use of pelvic compression devices such as binders is recommended as an early strategy to stabilize the pelvic ring and decrease the amount of pelvic hemorrhage in managing pelvic fractures (Coccolini et al, 2017; Jarvis et al, 2020; Pap et al, 2020). A study of inhospital and prehospital pelvic compression device use at U.S. Level I trauma centers found that prehospital pelvic compression devices were not applied to all suspected pelvic fractures (Jarvis et al, 2020). Similarly, Kuner found that only one-third of patients with pelvic fractures assigned to the resuscitation room of a Level I trauma center had a pelvic compression device applied (Kuner et al, 2021).…”
Section: Discussionmentioning
confidence: 99%